2018
DOI: 10.1371/journal.pone.0192207
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of fungal partners to incipient Cecropia-tree ant colonies

Abstract: Ascomycete fungi in the nests of ants inhabiting plants (= myrmecophytes) are very often cultivated by the ants in small patches and used as food source. Where these fungi come from is not known yet. Two scenarios of fungus recruitment are possible: (1) random infection through spores or hyphal fragments from the environment, or (2) transmission from mother to daughter colonies by the foundress queen. It is also not known at which stage of the colony life cycle fungiculture is initiated, and whether the- symbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 58 publications
1
61
0
1
Order By: Relevance
“…Additionally, Chaetothyriales has been proposed to be part of a tripartite mutualism between ants and L. africana plants [76]. Our results support previous studies that have documented the prevalence of this fungus within ant dwellings [40,42,76]. Assessing whether this prevalent ant-nest associate benefits ants and/or host plants would be an interesting follow-up study.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Additionally, Chaetothyriales has been proposed to be part of a tripartite mutualism between ants and L. africana plants [76]. Our results support previous studies that have documented the prevalence of this fungus within ant dwellings [40,42,76]. Assessing whether this prevalent ant-nest associate benefits ants and/or host plants would be an interesting follow-up study.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, the fungal order Chaetothyriales was in high abundance inside A. alfari nests (figure 4c). It has been proposed that founding queens carry Chaetothyriales fungal patches inside their infrabuccal pocket; however, whether these fungi are actively or passively transmitted is yet to be determined [42]. Chaetothyriales plays an important role in helping ants build their carton material and is a food source for the colony pupae and workers in some ant species [42,75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ant species that invest in smaller workers may be better at scrutinizing the surface of their host plant and removing small sap sucking insects 27 , but worse at fending off larger insects and vertebrates. In addition to plant dimensions, worker morphology may depend on food resources provided to the colony via food bodies 2 or nutritious pith called parenchyma 28,29 – plants providing more nutrition may produce larger workers. Morphometric analysis of the non- Cecropia -inhabiting congener Azteca trigona revealed that workers were dimorphic 30 , but worker size and allometry and their relation to plant traits have not been formally described in A .…”
Section: Introductionmentioning
confidence: 99%